Lipid arrays identify myelin-derived lipids and lipid complexes as prominent targets for oligoclonal band antibodies in multiple sclerosis. - Brennan, K; Galban-Horcajo, F; Rinaldi, S; O'Leary, C; Goodyear, C; Kalna, G; Arthur, A; Elliot, C; Barnett, S; Linington, C; Bennett, J; Owens, G; et al. (2011)
The presence of oligoclonal bands of IgG (OCB) in cerebrospinal fluid (CSF) is used to establish a diagnosis of multiple sclerosis (MS), but their specificity has remained an enigma since its first description over forty years ago. We now report that the use of lipid arrays identifies heteromeric complexes of myelin derived lipids as a prominent target for this intrathecal B cell response.